Platelet lysates scaffolds prepared by supercritical fluid technology as autologous templates for cartilage regeneration - Duarte, Ana Rita C. (2012)
The tissue engineering strategy proposed in this work regards the development of a novel autologous scaffold based on platelet lysates (PLs) with the ultimate goal of promoting the regeneration of an orthopaedic osteochondral interface. PLs are a high concentration of platelets in a small volume of plasma that, when activated, release several growth factors (GFs). Most of current PLs-based hydrogels present several limitations, specifically the lack of stability, the constant shrinking in culture and the need of activation with animal-derived thrombin. This study represents a major breakthrough as it demonstrates that a stable scaffold can be prepared only from PLs, thus acting simultaneously as a template for cell colonization and as multiple GF release system. The PL scaffolds, crosslinked with genipin were prepared by supercritical fluid assisted phase inversion at 100 bar and 40 °C. The morphological properties of the scaffolds were assessed and in vitro GF release profile was studied by micro BCA and ELISA assays.Scaffolds were seeded with human adipose-derived stem cells (hASCs) and cultured in vitro up to 28 days. Cell viability and proliferation were assessed as well as histology and immunohistochemistry. Results showed the deposition of cartilage extracellular matrix and the expression of chondrogenic gene makers, demonstrating the feasibility of the constructs to simultaneously provide architectural support and biological cues to promote chondrogenic differentiation.